THE PHENOMENON OF ADULT LEARNING THROUGH THE PRISM OF MODERN SOCIO-CULTURAL REALITIES - Dudka, Tetiana (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The article touches upon one of the most significant andragogic problems – the peculiarities of the phenomenon of adult learning. The priority of the influence of socio-cultural realities on the organization and implementation of the tasks of teaching the adult target audience is emphasized. The latest trend is correlated with the modern demands of the labour market and the current challenges of scientific and technological progress. The purpose of the study is to theoretically reflect on the problem of the influence of modern socio-cultural realities on the peculiarities of the organization and implementation of the tasks of adult learning. The purpose of scientific research is determined by the need to implement a complex theoretical analysis of the stated topic from an andragogical perspective, which makes it possible to correlate the research material with a whole spectrum of endogenous and exogenous factors that determine the peculiarities of the phenomenological nature. The significance of the influence on the personal level of the motivation component, which can take on the role of a decisive component at the level of effective implementation of educational tasks, has been considered in detail. During the problem presentation, attention is focused on the key differences of adult cognitive subjects, which are considered at the stage of organization and implementation of the educational process for them. The research procedure involved a combination of appropriate methodological tools presented at the level of methods of induction, deduction, comparative analysis, and problem statement. Due to the involvement of such a wide range of research methods, it was possible to single out the peculiarities of adult learning from the andragogical-psychological perspective of the study. This once again confirmed the interdisciplinary nature of the outlined topic. Attention is focused on the importance of the competence approach focused on the implementation of the tasks of teaching adults. This makes it possible to strengthen the practical component, as well as promote the development of value orientations and personal qualities of subjects of cognition. The result of the study was the design of an adult learning model, represented by the following component structure: self-awareness, motivation, purpose (educational, developmental, and educational), educational goals (knowledge, abilities, and skills), self-study, experience of educational, and professional activities. The conclusions were made that today’s socio-cultural realities have actualized the perception of the phenomenon of adult learning not only from the standpoint of the perspective of profession obtaining but above all from the conditions of ensuring its functioning in terms of market competition. The identified situation at the phenomenological level was closely linked with continuous learning – the driving force of socio-cultural progress